Novel Nonlinear Suspension Based on Concept of Origami Metastructures: Theoretical and Experimental Investigations - Antonio Zippo; Giovanni Iarriccio; Moslem Molaie; Francesco Pellicano (Vibration)
This study presents a comprehensive investigation of an innovative mechanical system inspired by recent advancements in metamaterials; more specifically, the work is focused on origami-type structures due to their intriguing mechanical properties. Originating from specific fields such as aerospace for their lightweight and foldable characteristics, origami mechanical devices exhibit unique nonlinear stiffness; in particular, when suitably designed, they show Quasi-Zero Stiffness (QZS) characteristics within a specific working range. The QZS property, aligned with the High Static Low Dynamic (HSLD) stiffness concept, suggests promising applications such as a low-frequency mechanical passive vibration isolator. The study explores the vibration isolation characteristics of origami-type suspensions, with a particular emphasis on their potential application as low-frequency passive vibration isolators. The Kresling Origami Module (KOM) has been selected for its compactness and compatibility with 3D printers. A detailed analysis using 3D CAD, Finite Element Analysis, and experimental testing has been carried out. The investigation includes the analysis of the influence of geometric parameters on the nonlinear force–displacement curve. Multibody simulations validate the low-frequency isolation properties within the QZS region, as well as disparities in dynamic properties beyond the QZS range. The study underscores the transformative potential of origami-type metamaterials in enhancing low-frequency vibration isolation technology. It also highlights challenges related to material properties and loading mass variations, providing valuable insights for future developments in this promising field.